Study of Dominance in the Foramen of Human Crania in Maharashtra Region - M. M. Peerzade; S. P. Fulari; G. S. Chakre; N.B. Masaram; W. F. Hiroli, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: 104 non - pathological dried adult cranial bases studied for dominance of various foramina by using hand lens. Jugular foramina (70.19%), Superior Orbital Fissure (30.2%), Foramina ovale (32.3%), Carotid Canal (21.5%), optic canal (4%) were dominant on right side, statistically highly significant (P<0.01) with Chi. Square (x2) goodness of fit test. While Inferior orbital fissure (19.38%), foramen Rotundum (25%), foramina spinosum (24.7%), stylomastoid foramina (14.4%), internal acoustic meatus (20.3%) were dominant on left side & statistically highly significant (P<0.01) with Chi. Square (x2) goodness of fit test. This study will certainly help the radiologists because CT scan, MRI does not show exact footage of the foramina, moreover the dominance of these foramina will also help the Neurosurgeons during the surgery of basal crania. Moreover Medico- legal expert, Anthropologist, Anatomist to specify the Maharashtra state crania from other state crania.